Distribusi Nitrat dan Fosfat Secara Spasial dan Temporal Saat Musim Barat Di Permukaan Perairan Teluk Benoa, Bali - Ni Wayan Sukma Taraning Rahayu; I Gede Hendrawan; Yulianto Suteja (Journal of Marine and Aquatic Sciences, 2018)
Benoa Bay is an estuary that effected by pollutan from river and human activity. Reasearch on spatial and temporal distribution of nitrate and phosphate has been conducted in Benoa Bay. Data was collected at water surface during ebb from December 2016 to Februari 2017. There were19 Sampling pointlocated in Benoa Bay and 6 pointslocated in rivers around Benoa Bay. Nitrate was analysed using Brucine method and phosphate was analysed using Amm-Molybdat method. The concentration of nitrate from December 2016 to February 2017 ranged from 0,036 mg/L to 1,154 mg/L and the concentration of phosphate ranged from undetectedto 0,739 mg/L. The concentration of nitrate at rivers ranged from undetectedto 3,584 mg/L andthe concentration of phosphate ranged from undetectedto2,405 mg/L. The concentration of nitrate and phosphate from December 2016 to February 2017 was fluctuating and the highest average concentration of nitrat and phosphate was found in February 2017. These was due to high rainfall in February 2017 and cause a lot of organic matters carried by the rivers into Benoa Bay. The highest distribution concentration of nitrate and phosphate was found around estuary. These due to input of organic matters from mainland through the rivers. Based on water quality standards of Bali Goverment, the concentration of nitrate and phosphate was exceeds the seawater quality standart.